Characterization and comparison of the thermophysical property of ternary and quaternary salt mixtures for solar thermal power plant applications - Collins C. Kwasi-Effah; Osarobo Ighodaro; Henry O. Egware; Albert I. Obanor (Results in Engineering, 2022)
Molten salts offer superior thermal properties to synthetic mineral oil, making them suitable for use directly as heat transfer fluids in solar thermal power plants. In comparison to the binary salt mixture, the ternary and quaternary salt mixtures have demonstrated the ability to attain a low melting temperature of less than 100 °C. However, the thermophysical characteristics of the ternary and quaternary salt mixtures with respect to their usage in solar thermal power plant applications have remained unclear in most literature findings. This is due to similar thermophysical behavior and limited study of quaternary salt mixtures. Therefore, to fill this gap, the processing and testing of a class of novel ternary and quaternary salt mixtures were conducted to obtain the distinct thermophysical characteristics and trade-offs of the salt mixtures. The benefits and drawbacks of each mixture type are presented. Furthermore, experimental data was utilized to develop models to predict the thermophysical properties of the salt mixtures.